The State of Conservation in North America’s Boreal Forest: Issues and Opportunities - Wells, Jeffrey V.; Dawson, Natalie; Culver, Nada; Reid, Frederic A.; Morgan Siegers, Shaunna (Frontiers in Forests and Global Change, 2020)
The North American Boreal Forest biome has been recognized as containing some of the highest proportions of intact, primary forest left on Earth. Over 6 million km² of the Boreal Forest biome is found in Canada (5.5 million km²) and the U.S. (0.74 million km²) across 10 provinces and territories and one U.S. state (Alaska). All of it is within the traditional territories of hundreds of Indigenous governments, many of whom are now asserting their rights to make decisions about its future and current land-use including for conservation and development. The biome is considered to be 80% intact and between 8% and 13% formally protected. The North American Boreal Forest biome’s intactness has allowed it to retain many globally significant conservation features including long-distance mammal and fish migrations, healthy populations of large predators, one to three billion nesting birds, some of the world’s largest lakes and North America’s longest undammed rivers, massive stores of carbon and ecological functionality. The biome’s forests, minerals, and hydropower potential are also recognized as economic opportunities so that the industrial footprint is rapidly increasing, sometimes without careful land-use planning decisions. Indigenous, federal, state, provincial and territorial governments and conservation organizations have strived over recent decades to recognize the conservation opportunity inherent in such a still-intact landscape, resulting in implementation of some of the world’s largest land conservation set-asides. Indigenous governments, in particular, have been at the forefront in developing and implementing world-leading, modern land-use plans that achieve land conservation at massive scales. Supporting efforts to ensure that a high proportion of North America’s Boreal Forest biome is protected and remains as intact habitat with unimpeded ecosystem processes should be a priority of the global conservation community. Federal, state, and provincial/territorial governments should support Indigenous protected area proposals, vastly increase financial support for Indigenous government land conservation and stewardship activities, and should develop new protected area co-management models with Indigenous governments. Governments should also be strongly advocating for raising the global Convention on Biological Diversity protected area goal to at least 30% by 2030.